The effect of blood and synthetic tissue fluid on the microhardness of ProRoot MTA, OrthoMTA and RetroMTA - Noushin Shokouhinejad; Hassan Razmi; Mehrfam Khoshkhounejad; Pegah Firouzmanesh (Tehran University of Medical Sciences, 2017)
Background and Aims: The aim of this study was to assess the microhardness of BioMTA (OrthoMTA, RetroMTA) in distances of 0.5, 2 and 3.5 mm from the exposed surface to blood, phosphate buffer saline (PBS) or distilled water and to compare to that of ProRoot MTA. Materials and Methods: One hundred and thirty five semicylindrical polymethyl methacrylate were filled with either ProRoot MTA, OrthoMTA, or RetroMTA. Fifteen molds in each group were exposed to blood, 15 molds to PBS and the other 15 to distilled water. The microhardness of the materials at 0.5, 2 and 3.5 mm distance from the exposed surface to phosphate-buffered saline (PBS) as a synthetic tissue fluid, blood, and distilled water was assessed. The data were analyzed using one-way ANOVA and Tukey post hoc tests. Results: Exposure to blood significantly decreased the microhardness of all materials at all three points of 0.5, 2 and 3.5 mm (P<0.001). At level of 0.5 and 2 mm distant from blood, OrthoMTA showed significantly the least microhardness value; however, at the point of 3.5 mm, the microhardness of RetroMTA was higher than the two other materials (P<0.001). After exposure of samples to distilled water or PBS, no significant difference was found between the materials at any levels of 0.5, 2, and 3.5 mm (P<0.01). Conclusion: Blood exposure resulted in the decrease of microhardness of internal part of the materials.